Development of SCAR-CPS markers linked to tolerance-sensitivity to Fusicoccum in almond - Martins M.; Sarmento D.; Oliveira M.M.; Batlle I.; Vargas F.J. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
Fusicoccum amygdali is responsible for Fusicoccum canker, a damaging and economically important disease in almond (Prunus dulcis Mill.) orchards around the Mediterranean region. Fourteen almond cultivars classified as tolerant (7) or sensitive (7) to Fusicoccum were screened with 120 RAPD primers. Polymorphic bands were assessed for co-segregation with tolerant or sensitive phenotypes using 30 seedlings obtained from a 'Masbovera' (tolerant) x 'Lauranne' (sensitive) cross. Three RAPD markers linked to tolerance (OPD-19300 and OPA-08900) or sensitivity (OPD-19500) to Fusicoccum in almond were identified. SCAR primers were developed but polymorphism between the two groups was lost. The possibility of developing CAPS will be analysed.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)